2017
DOI: 10.1161/circresaha.117.310812
|View full text |Cite
|
Sign up to set email alerts
|

P2Y 2 Nucleotide Receptor Prompts Human Cardiac Progenitor Cell Activation by Modulating Hippo Signaling

Abstract: Rationale Autologous stem cell therapy using human c-Kit+ cardiac progenitor cells (hCPCs) is a promising therapeutic approach for treatment of heart failure (HF). However, hCPCs derived from aged HF patients with genetic predispositions and/or comorbidities of chronic diseases exhibit poor proliferative and migratory capabilities, which impairs overall reparative potential for injured myocardium. Therefore, empowering functionally compromised hCPCs with pro-regenerative molecules ex vivo is crucial for improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 56 publications
0
26
0
Order By: Relevance
“…The purinergic receptor signaling was crucial for the ATP‐mediated NLRP3 activation in allograft rejection . Interestingly, the purinergic receptors induced cell proliferation and migration in injured tissues by regulating YAP activation, suggesting that there is a crosstalk between purinergic receptors and the Hippo‐YAP pathway. Moreover, the hypoxia‐inducible factors regulated their target genes, leading to resistance to ischemia and controlling excessive inflammation, which may interact with YAP under hypoxic conditions .…”
Section: Discussionmentioning
confidence: 99%
“…The purinergic receptor signaling was crucial for the ATP‐mediated NLRP3 activation in allograft rejection . Interestingly, the purinergic receptors induced cell proliferation and migration in injured tissues by regulating YAP activation, suggesting that there is a crosstalk between purinergic receptors and the Hippo‐YAP pathway. Moreover, the hypoxia‐inducible factors regulated their target genes, leading to resistance to ischemia and controlling excessive inflammation, which may interact with YAP under hypoxic conditions .…”
Section: Discussionmentioning
confidence: 99%
“…GPCR signaling is one of the major upstream signals that regulate YAP/TAZ activation in a variety of systems, including PDAC 31 . In this context, the expression of genes encoding the lysophosphatidic acid (LPA) receptor GPR87 86 , the purinergic GPCR P2Y 2 R 87 and the GPCR agonist EDN2 (endothelin 2) 57 , a downstream target of YAP, are also associated with an unfavorable prognosis in PDAC. A recent independent study confirmed that overexpression of GPR87 is correlated with a poor prognosis in PDAC 88 .…”
Section: Molecules Downstream and Upstream Of Yap Are Unfavorable Promentioning
confidence: 99%
“…P2Y 2 receptor (P2Y 2 R) is a purinergic GPCR that regulates Gα q/11 -PKC signaling to control the flow of Ca 2+ and K + ions 90 . The P2Y 2 R-PKC axis activates YAP1 by inhibiting LATS1/2 and subsequently promote cell proliferation in human c-Kit + cardiac progenitor cells (hCPCs), which helps to rescue CM from damages 91 , 92 . Moreover, the GPCR agonist neurotensin attenuates YAP1 phosphorylation at Ser127/397 and augments YAP1 nuclear localization via PKD signaling 93 .…”
Section: Interaction Of Hippo-yap1/taz Signaling With the Gpcr Pathwamentioning
confidence: 99%